Amine-grafted mesoporous copper silicates as recyclable solid amine sorbents for post-combustion CO2 capture. (15th July 2017) - Ren, Yanping; Ding, Ruiyu; Yue, Hairong; Tang, Siyang; Liu, Changjun; Zhao, Jinbo; Lin, Wen; Liang, Bin
Graphical abstract: Highlights: A novel amine-grafted mesoporous coppersilicate named CSNS-TA was synthesized for CO2 capture. The CO2 adsorption was at relatively mild conditions, e.g., ambient temperature and pressure. CSNS-TA presents high CO2 capture capacity, recyclability and long-term stability. The high efficiency was proposed from the unique microstructure, stable amines grafted on CSNS. Abstract: Amine-functionalized nanomaterials have significant potential in CO2 capture technology because of their low energy consumption, stable performance, and high regeneration capacity. Novel amine-functionalized adsorbents composed of copper silicate nanospheres (CSNSs) grafted with mono-, di- and tri-aminosilanes were synthesized for CO2 capture. The synthetic process and formation mechanism were systematically investigated using transmission electron microscopy, X-ray photoelectron spectroscopy, fourier transform infrared spectroscopy, and N2 physisorption analysis, etc. The copper silicates with rich surface hydroxyl groups, significant surface areas and mesoporous structures facilitated chemical modification of amines, leading to a high CO2 adsorption capacity (a maximum CO2 uptake of 47.88 mg/g) and excellent cyclic regenerability (maximum deviation of 3.51% after 20-times test) for CSNS-TA. In addition, the CO2 capture process was carried out under relatively mild conditions, e.g., adsorption at 298 K, desorption at 373 K and ambient pressure, suggesting that these amine-modified CSNSs have potential as solid sorbents for CO2 capture.